Barriers and Opportunities in Fostering Pragmatic Competence in the Digital Age - Kaur, Parwinder; Fanani, Achmad (Indonesian Scientific Publication, 2024)
This study reviews the development of pragmatic competence within digital communication platforms, aiming to synthesize evidence from recent literature and assess both opportunities and challenges. The review employs a systematic methodology, drawing from databases including JSTOR, ScienceDirect, Google Scholar, and Wiley Online Library, and applying inclusion criteria covering studies published between 2015 and 2024. The findings highlight five central themes: authenticity and context, intercultural diversity, personalization and adaptivity, technological barriers and access gaps, and the potential of emerging technologies such as artificial intelligence, gaming, and virtual reality. Evidence shows that authentic digital contexts and intercultural exchanges foster pragmatic awareness, while adaptive learning technologies enhance individualized instruction. However, significant barriers persist, including infrastructural inequalities, socio-economic disparities, and digital literacy gaps that constrain equitable access to pragmatic learning. Comparative studies suggest that learners in technologically advanced regions benefit more readily from these innovations than those in developing contexts. The discussion links these findings to pragmatic theory, emphasizing the role of systemic factors such as policy and infrastructure, and identifies the need for inclusive strategies to ensure equal opportunities. Recommendations include the development of longitudinal and cross-cultural research, as well as practical integration of advanced technologies into mainstream education. Overall, the study underscores the urgent need for combined strategies that integrate authenticity, intercultural awareness, personalization, and technological innovation to enhance pragmatic competence in digital communication.